Effect of Limited Watering on Survival and Establishment of Bamboo (Dendrocalamus strictus Roxb.) on Denuded Hills of Aravallis - Mathur, Indra Jit; Mahnot, S. C. (Indian Forester, 2000)
A field study was undertaken to evaluate the effect of limited watering levels on survival and initial establishment and growth of bamboo during July 1990 to November, 1992. The treatments consisted of four levels of water W0, IW1 , IW2 and SW10 (0, 1, 2 and 10 litres water). One and two litres of water was applied through sub-soil injectors and 10 litres as surface application. In all 7 watering were provided in each year during October (at an interval of 45 days) and February to June (at an interval of30 days). In the first year, SW10 treatment recorded maximum survival, which was statistically at part with IW2. Watering in the second year had no effect on survival. However, successive increase in watering levels had significantly enhanced production of culms. At the end of experimentation (28 MAP) treatment SW 10 produced maximum culms with highest diameter. However, treatment IW2 came out at par with SW10 for many important parameters.